Developing framework for capabilities related to supporting management discipline that contributes to r&d in public organizations of Pakistan - Asim, Zeeshan (2019)
Research and development R&D under the boundaries of management scope has become a crucial aspect for individual, organizational and global level. R&D has long considered as a top priority for developing countries. However, R&D across developing countries confronts vital deficiencies in classifying capabilities to address capability failure issue. As result of such problem, there is potential demand among public organizations for creating theoretical model dealing R&D at organizational level. The prime objective of this research is to classify the capabilities related to supporting management discipline that adds their influence on R&D, To analyze the interrelationship among the capabilities related to supporting management discipline for R&D in Pakistan Public Organizations and To prioritize the capabilities that involve at R&D in public organizations based on their interdependency in case of Pakistan . To accomplish the primary objective, the research comprise on theoretical and empirical studies: General literature review; Systematic literature review gathering capabilities related to supporting management disciplines that involve in R&D; Focus group discussion applied for refining capabilities under country-specific view; Applying proposed model in case of Pakistan public organization to reconfigure R&D orientation to confront future challenges. Competitive progression in any R&D firm does have cross-cultural implication specific to country within which the R&D functioned since is this study draw the case of R&D in Pakistan public organization. Therefore, Focus group technique adapted to refining relevant capabilities related to knowledge innovation and technology management as “supporting management discipline”. These capabilities gathered from the systematic literature review (PRISMA and Co-word analysis). The experts nominated from various research centers that include universities, public organizations. Furthermore, based on focus group results the interrelationship and prioritization of capabilities can be formulate through DANP techniques. The DANP (DEMATEL Based ANP) technique utilizes multidisciplinary experts that allow general model fitting specifically to R&D’s in public organization. The study concluded, by filling the potential gap that occurs in shape of capability failure. Key finding of this study is to draws novel Framework on infrastructural, processes and strategic perspective related to capabilities that belongs to knowledge, innovation and technology management along with behavior of their resources that influence indirectly on R&D. The capabilities perspective as criteria’s allowing decision makers to assess the vital deficiencies in classifying capabilities to address capability failure issue. This research enables policymakers to developed R&D framework that might be useful for other low privilege developing countries where state driven R&D model plays a crucial role in developing national science policy.